An E-band CMOS frequency quadrupler with 1.7-dBm output power and 45-dB fundamental suppression. (1st September 2022) - Liao, Xiaofei; Zhao, Dixian; You, Xiaohu
Abstract: This paper presents an E-band frequency quadrupler in 40-nm CMOS technology. The circuit employs two push–push frequency doublers and two single-stage neutralized amplifiers. The pseudo-differential class-B biased cascode topology is adopted for the frequency doubler, which improves the reverse isolation and the conversion gain. Neutralization technique is applied to increase the stability and the power gain of the amplifiers simultaneously. The stacked transformers are used for single-ended-to-differential transformation as well as output bandpass filtering. The output bandpass filter enhances the 4th-harmonic output power, while rejecting the undesired harmonics, especially the 2nd harmonic. The core chip is 0.23 mm 2 in size and consumes 34 mW. The measured 4th harmonic achieves a maximum output power of 1.7 dBm with a peak conversion gain of 3.4 dB at 76 GHz. The fundamental and 2nd-harmonic suppressions of over 45 and 20 dB are achieved for the spectrum from 74 to 82 GHz, respectively.